ABOUT SOME CRIMINAL LEGAL PROBLEMS OF COUNTERING ENVIRONMENTAL OFFENSE IN THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2024)
The article analyzes the fight against environmental violations through the prism of criminal law science and environmental law. The purpose of this article is to analyze a number of aspects of criminal liability in the environmental sphere provided for in Kazakh legislation, which have a certain scientific significance. Some theoretical provisions are also presented that reveal its content. It is recognized that Kazakhstan, as a stable democratic state, respects human rights and the primacy of the law in the context of further transformations in the environmental sphere. Through the presented methods of comparative, structural-systemic, historical and other forms of analysis, the subject area of research is determined, which is based on the recommendations of international law and UN institutions in the environmental field, focused on the sustainable development of Kazakhstan. In the process of analysis, the presence of problematic issues of a criminal legal nature in combating environmental offenses is noted, requiring a balanced assessment in determining the degree of guilt and measures of criminal liability. At the moment, in the context of active development in the Republic of Kazakhstan, new legal relations are emerging, and the process of improving the procedure for legal regulation of existing ones is underway. In this correlation, elements of the permanent development of new legal specific forms are seen. Following the theorists, it is correct to recognize that environmental legal relations are a state where mutual rights and obligations arise between subjects regarding state-protected interests in the environmental sphere. Practical implementation. The above aspects contributed to the active introduction of new theoretical and practical issues and norms into environmental legislation. It can also be stated that the correctness in the definition of the concept of “environmental offense” led to further correlation of the norms of all branches of legislation. Key words: national legislation, international law, combating environmental violations, degree of responsibility, degree of guilty behavior, sanctions.